Challenges and Opportunities in Millet Production: A Sustainable Perspective - Kumari, Megha; Singh, Teekam; Devi, Ayekpam Dollina (Chronicle of Bioresource Management, 2023)
Millet are nutrient-rich, climate-resilient crops with great potential for food security and sustainable agriculture. However, its cultivation faces several challenges that impact its productivity and market potential. Low grain yield compared to major cereals, susceptibility to erratic weather patterns, pest attacks, and limited availability of improved seed varieties hinder widespread adoption. Additionally, inadequate processing facilities and weak supply chains make commercialization difficult, reducing profitability for farmers. Consumer preference for other staple grains, along with a lack of awareness about the nutritional and environmental benefits of millet, further limits demand. Limited research and financial support have also slowed advancements in cultivation techniques and value addition. Addressing these issues requires better farming practices, investment in crop improvement programs, modern processing technologies, and initiatives to educate consumers.